PENGARUH EFIKASI DIRI DAN REGULASI DIRI TERHADAP HASIL BELAJAR MATEMATKA SISWA KELAS X SMA ALKHAIRAAT 1 PALU - Aflan Rustam; Dewi Sri Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This type of research is ex-post facto which is causal. The population in this study were all students of class X at Alkhairaat High School 1 Palu. The population in this study was less than 100, namely 52 students. By this, the researcher did not conduct sampling in this study, so this study was a population research. The research variables included self-efficacy (X1), self-regulation (X2), namely as independent variables and mathematics learning outcomes (Y) as the dependent variable. Data collection techniques using documentation, tests and questionnaires. The prerequisite test shows that the data in this study are normally distributed, so hypothesis testing uses multiple regression analysis through the SPSS 23 application. The results of this study indicate that: 1) the level of self-efficacy of students is 71 in the medium category. 2) the level of self-regulation of students is 141 in the medium category. 3) the level of mathematics learning outcomes of students is 63 in the medium category. 4) significant value of self-efficacy of 0,000 <0,05 and a regression coefficient of 0,446 with a positive value, then H0 is rejected and Ha is accepted meaning self-efficacy has a positive effect on mathematics learning outcomes. 4) significant value of self-regulation of 0,000 <0,05 and has a regression coefficient value of 0,264 with a positive value, then H0 is rejected and Ha is accepted meaning self regulation has a positive effect on the learning outcomes of mathematics. 5) R Square coefficient or coefficient of determination shows that the percentage contribution of the influence of independent variables is 58.5%. This shows that self-efficacy and self-regulation influence the mathematics learning outcomes by 58.5% and the other 41.5% are influenced by variables outside of self-efficacy and regulation